2016
DOI: 10.6004/jnccn.2016.0116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Prostate Cancer in a Functional Eunuch

Abstract: Background Eunuchs rarely, if ever, develop prostate cancer (CaP). This article reports on a 62-year-old functional eunuch from prepubertal mumps orchitis who developed clinically localized CaP. Methods Serum and CaP and benign prostate tissue androgen levels were measured using a validated liquid chromatography-tandem mass spectrometry assay. The assay measures testosterone; dihydrotestosterone (DHT); the adrenal androgens, androstenedione and dehydroepiandrosterone; and the androgen metabolites, androstero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Therefore, LC‐MS/MS was performed to determine if media composition impacted T metabolism. LAPC‐4 cells were used because LAPC‐4 cells express SRD5A enzymes that metabolize T to DHT (Figure A, modified from ), unlike LNCaP or C4‐2 cells, which cannot metabolize T to DHT . LC‐MS/MS revealed that LAPC‐4 cells cultured for 6 days in CM alone produced higher levels of DHT (all P ‐values <0.05; Supplemental Table S5) than LAPC‐4 cells cultured for 6 days in SFM or CSM alone (Figures B and C, and Supplemental Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, LC‐MS/MS was performed to determine if media composition impacted T metabolism. LAPC‐4 cells were used because LAPC‐4 cells express SRD5A enzymes that metabolize T to DHT (Figure A, modified from ), unlike LNCaP or C4‐2 cells, which cannot metabolize T to DHT . LC‐MS/MS revealed that LAPC‐4 cells cultured for 6 days in CM alone produced higher levels of DHT (all P ‐values <0.05; Supplemental Table S5) than LAPC‐4 cells cultured for 6 days in SFM or CSM alone (Figures B and C, and Supplemental Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…CRPC is driven in part by DHT derived from intratumoral metabolism of adrenal androgens . DHT biosynthesis involves three androgen biosynthesis pathways (Figure , modified from). In the frontdoor pathway, the adrenal androgens (dehydroepiandrosterone [DHEA] and androstenedione [ASD]) are T precursors, and T is reduced by 5α‐reductases (SRD5A) to form DHT.…”
Section: Introductionmentioning
confidence: 99%
“…Androgen biosynthesis pathways (modified from). Prostate cancer (CaP) cells can produce dihydrotestosterone (DHT) via three androgen biosynthesis pathways.…”
Section: Introductionmentioning
confidence: 99%
“…They found a significant positive correlation between the local prostatic serum DHT levels and both prostate weight and peripheral serum levels. As prostate cancer is able to synthesize DHT in an intracrine manner, the presence of cancer could lead to biased assessments. For this reason, study regarding relationship between sex steroid concentrations and prostate enlargement requires exclusion of the presence of cancer through a complete pathological examination.…”
Section: Introductionmentioning
confidence: 99%